2022
DOI: 10.3390/nano12213780
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nanomaterials with Different Dimensions as Lubricant Additives

Abstract: Lubricant additives can effectively enhance the performance and environmental adaptability of lubricants and reduce the energy loss and machine wear caused by friction. Nanomaterials, as important additive materials, have an essential role in the research and development of new lubricants, whose lubrication performances and mechanisms are not only related to their physical and chemical properties, but also influenced by the geometric shape. In this paper, the friction reduction and antiwear performances of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Utilizing lubricants has been proven to be one of the most effective approaches to solving the above problems. Generally, the lubricant is composed of two parts: the lubricating medium, which accounts for 70–95% and is a kind of basic lubricant with limited effect, and lubricating additives, which though comprise only a tiny percentage of the lubricant, tremendously enhance the tribological properties. , Consequently, exploration of the properties of various lubricant additives is particularly crucial. The boom in nanoscience has guided the study of lubricant additives at the micro level; surprisingly, numerous researchers have suggested that as the size of lubricant additives diminishes persistently, there is a dramatic increase in the tribological properties, which not only easily breaks the upper limit of properties of traditional lubricant additives but also exhibits excellent performance even in harsh working conditions, such as heavy load, high temperature, and drastic shear at a high speed.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing lubricants has been proven to be one of the most effective approaches to solving the above problems. Generally, the lubricant is composed of two parts: the lubricating medium, which accounts for 70–95% and is a kind of basic lubricant with limited effect, and lubricating additives, which though comprise only a tiny percentage of the lubricant, tremendously enhance the tribological properties. , Consequently, exploration of the properties of various lubricant additives is particularly crucial. The boom in nanoscience has guided the study of lubricant additives at the micro level; surprisingly, numerous researchers have suggested that as the size of lubricant additives diminishes persistently, there is a dramatic increase in the tribological properties, which not only easily breaks the upper limit of properties of traditional lubricant additives but also exhibits excellent performance even in harsh working conditions, such as heavy load, high temperature, and drastic shear at a high speed.…”
Section: Introductionmentioning
confidence: 99%
“…The wear protection and friction reduction ability can decrease because the agglomerated nanoparticles cannot enter the contact zone. 82,83 This concept could be applied to spherical metal and metal oxide additives, whose main mechanisms are ball bearing and surface enhancement (polishing and mending effects). 84 For film-forming antiwear additives, it is argued that how quickly the nanoparticles can form the protective layer to prevent early wear and the durability of the tribofilm are more important than the additive dispersibility, as pointed out in this study.…”
Section: Relationship Between Dispersibility and Wear Performance Of ...mentioning
confidence: 99%
“…The use of lignin nanoparticles (LNPs) instead of bulk lignin overcomes the limitations of lignin stemming from its heterogeneous structure and wide molecular weight distribution, which are two important factors affecting the efficiency of lignin as a lubricating additive. 33 Additionally, introducing lignin in the form of nanoparticles can improve its dispersibility, while the spherical geometry can result in rolling bearing effects. 33 In addition, the hydroxymethylation of lignin serves the purpose of increasing its hydroxyl content while adding hydroxymethyl moieties adjacent to the phenolic structure of lignin as cross-linking sites, helping to increase the hydroxyl content of lignin after hydrothermal cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…33 Additionally, introducing lignin in the form of nanoparticles can improve its dispersibility, while the spherical geometry can result in rolling bearing effects. 33 In addition, the hydroxymethylation of lignin serves the purpose of increasing its hydroxyl content while adding hydroxymethyl moieties adjacent to the phenolic structure of lignin as cross-linking sites, helping to increase the hydroxyl content of lignin after hydrothermal cross-linking. Therefore, we prepared composite powders of MoS 2 -HLNPs via a simple and green hydrothermal synthesis route, where the final product could combine the structural stability of biomass-based nanoparticles with the lubricant performance of the inorganic phase.…”
Section: Introductionmentioning
confidence: 99%